Understanding preschoolers’ word learning success in different scenarios: disambiguation meets statistical learning and eBook reading - Pino Escobar, Gloria; Tuninetti, Alba; Antoniou, Mark; Escudero, Paola (Frontiers in Psychology, 2023)
Children’s ability to learn new words during their preschool years is crucial for further academic success. Previous research suggests that children rely on different learning mechanisms to acquire new words depending on the available context and linguistic information. To date, there is limited research integrating different paradigms to provide a cohesive view of the mechanisms and processes involved in preschool children’s word learning. We presented 4 year-old children (n = 47) with one of three different novel word-learning scenarios to test their ability to connect novel words to their correspondent referents without explicit instruction to do so. The scenarios were tested with three exposure conditions of different nature: (i) mutual exclusivity–target novel word-referent pair presented with a familiar referent, prompting fast-mapping via disambiguation, (ii) cross-situational–target novel word-referent pair presented next to an unfamiliar referent prompting statistically tracking the target pairs across trials, and (iii) eBook - target word-referent pairs presented within an audio-visual electronic storybook (eBook), prompting inferring meaning incidentally. Results show children succeed at learning the new words above chance in all three scenarios, with higher performance in eBook and mutual exclusivity than in cross-situational word learning. This illustrates children’s astounding ability to learn while coping with uncertainty and varying degrees of ambiguity, which are common in real-world situations. Findings extend our understanding of how preschoolers learn new words more or less successfully depending on specific word learning scenarios, which should be taken into account when working on vocabulary development for school readiness in the preschool years.